Berberine Protects Human Retinal Pigment Epithelial Cells from Hydrogen Peroxide-Induced Oxidative Damage through Activation of AMPK - Li, Shuai (Int J Mol Sci, 2018)
Age-related macular degeneration (AMD) is the leading cause of central vision loss in the elderly with less effective treatment, especially for dry AMD (90% of AMD). Although the etiology of this disease is not well elucidated, increasing evidences indicate that excessive reactive oxygen species (ROS) impairing the physiological functions of retinal pigment epithelium (RPE) cells may be one of the main causes. Therefore, it could be a great strategy to find some drugs that can effectively protect RPE cells from oxidative damage which is desired to treat and slow the process of AMD. In the present study, a well-known traditional Chinese medicine berberine (BBR) was found to suppress hydrogen peroxide (H(2)O(2))-induced oxidative damage in D407 cells, a human RPE cell line. Pre-treatment of D407 cells with BBR significantly suppressed H(2)O(2)-induced cell apoptosis by restoring abnormal changes in nuclear morphology, preventing the decline of mitochondrial membrane potential, reducing lactate dehydrogenase release and inhibiting caspase 3/7 activities induced by H(2)O(2). Western blot analysis showed that BBR was able to stimulate the phosphorylation/activation of AMPK in a time- and dose-dependent manner in D407 cells, while treatment of cells with AMPK pathway inhibitor Compound C, or knockdown of the AMPK by specific siRNA blocked the effect of BBR. Similar results were obtained in primary cultured human RPE cells. Taken together, these results demonstrated that BBR was able to protect RPE cells against oxidative stress via the activation of AMPK pathway. Our findings also indicate the potential application of BBR in AMD treatment.